Implementasi Program Pengembangan Karakter dan Spiritual Melalui Lomba Keagamaan di Desa Limo Lamleuweung Aceh Besar - M Azrial Aksar; Arif Zakiyul Mubarak; Mussauwir; Aghyar; Dilaena Nur Barokah; Anggi Rapita Rahma Day; Nisya Kamila; Sari Novita; Salma; Wira Asfahani Merina (Jurnal Riset dan Pengabdian Masyarakat, 2025)
The character and spiritual development program through religiouscompetitions was implemented in Limo Lamleuweung Village, Aceh Besar,as part of the Real Work Lecture (KPM) activities. This program aims toinstill Islamic religious values and build positive character in elementaryschool children. There are three categories of competitions held, namelyreligious speeches, adhan, and short surah memorization. The results of thisprogram showed a significant positive impact, especially in increasing self-confidence, communication skills, and understanding of religion in children.In addition, this program also strengthened relations between residents andrevived religious traditions in the village.